The Pengaruh Pola Asuh Demokratis Orang Tua Pada Ketahanan Anak Sekolah Dasar Mengatasi Perundungan Di Denpasar - Octoviany, Christine; Winoto, Hery; Andriono, Takim; Wahyoedi, Soegeng (Satya Widya, 2024)
The background of this quantitative research stems from the increasing cases of bullying experienced by children. The objectives of this study are to address several questions: (1) Does the democratic parenting style influence child’s resilience? (2) Does the democratic parenting style influence bullying behavior? (3) Does a child's resilience play a role in overcoming bullying at school? and (4) Does a child's resilience mediates the influence of democratic parenting styles on bullying? The research population consists of 150 parents with primary school-aged children in Denpasar, Bali. This research was conducted in the third week of January 2023 to September 2023. Data collection instruments include questionnaires distributed to parents in both online Google Forms and physical questionnaire sheets. Data processing and mediation effect testing are analyzed using the SmartPLS version 4.0 software application. The research concludes that a democratic parenting style positively and significantly influences the resilience of elementary school children. This suggests that an increasingly better democratic parenting style can produce children with high self-resilience, enabling them to overcome bullying and other challenges they will face in their lives. However, statistically, the resilience of elementary school children does not mediate the influence of the democratic parenting style variable on the bullying variable.